Anonymity, Piracy and Counterfeiting in the Polish Language Publications in the Grand Duchy of Lithuania in the 2nd Half of the 16th Century - Petreikis, Tomas (Knygotyra, 2023)
On the grounds of the bibliographic analysis of the publications in the Polish language in the Grand Duchy of Lithuania in the second half of the 16th century, this article reconstructs the phenomena of anonymity, counterfeiting and piracy. In this country, the life of the printed media was fairly liberal and hardly restricted at all. In the course of political and religious struggles, authors, translators, publishers and compilers frequently preferred to conceal the data on the real authorship and typography in their publications. Political and religious factions had to consider the opinion of the ruler and their seniority; therefore, only anonymous impact on the public opinion allowed ensuring the defense of one’s attitudes and the desired impact on the society. This strategy of anonymity was protecting the stakeholders from getting into trouble, while also expanding the scope of commercial activity for the typographers. The phenomenon of piracy was also being promoted by the different legal regulation of the printed media in the Grand Duchy of Lithuania and the Kingdom of Poland, and, due to the physically vast distances, the feeling of impunity developed. The authors and typographers were acting honestly in such cases when the published literature contained no controversial materials, or when they had the solid backing of the powers, and also in the cases when legal protection of the printed media was ensured.